"Equal Discipleship" - Lu, Yifan (The ecumenical review, 2019)
Feminist theology is known for its various critical principles and methods of biblical interpretation. In the process of doing feminist biblical interpretation, feminist theologians have started to build their theological frameworks. This article takes the feminist biblical scholar Elisabeth Schüssler Fiorenza and her construction of the New Testament as an example. In her book Discipleship of Equals, Schüssler Fiorenza put forward the important viewpoint of "equal discipleship." This viewpoint provides a dialogue between Schüssler Fiorenza and the theological concerns of women in China. Like Schüssler Fiorenza, Chinese theologians have also noted the testimonies of Chinese women Christians in the development of the church. These can help female Christians realize who they are and the significance of being a member of the church. Christian Chinese traditional culture still influences the understanding of women's identity. This will be a significant challenge and task in practising Chinese feminist theology.